Strategy for Human Resource Management Development Based on Digital Transformation to Optimize the Performance of PT. Dirgantara Indonesia - Hidayat, Hidayat; Suhartono, Gunawan; Rukayat, Yayat (Asosiasi Ahli Administrasi Indonesia, 2025)
PT Dirgantara Indonesia (Persero) is an aerospace industry owned by the state. The accelerating speed of digital transformation nowadays has revolutionised businesses in how they digitally manage their information, automate processes, and enhance human capital productivity. The main aims for PT Dirgantara Indonesia are to reconcile the development strategies of HR and technological progress so that there is professional competence and organisational excellence in its workforce. This study explores the digital transformation principles that underlie HRM strategies in PT Dirgantara Indonesia. The study used a qualitative descriptive design, and the data were collected through field observations, interviews with HR managers, line managers, employees, and stakeholders. Click here for the full article. A semi-structured interview protocol was used in an effort to obtain deep insights from the participants about the process of incorporation digital transformation into HRM practices. The findings indicate that PT Dirgantara Indonesia has made strategic and systematic efforts to develop the human resources based on digital technology. Some of the significant initiatives include digitization of business processes, application of digitally integrated databases, and innovation-driven product and service development. It has also introduced hundreds of digital training and empowerment programs, automated manual processes, and changed internal rules to adapt to shifting digital market realities. The organizational leaders applied the APS-6 INDI 4.0 Assessment to evaluate the readiness of the organization for digital transformation, implemented immediate actions in areas where gaps were identified, and showed a continued necessity for them to adapt to new technology that will sustain performance at all levels.